USING PODCAST CONTENT FOR ONLINE DEBATE TO HONE SPEAKING ABILITIES - Suseno, Edy (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Many EFL students find it difficult to participate in debates. They find it challenging to speak clearly due to their pronunciation and vocabulary challenges. Ten freshmen participated in the therapy to fix it. They are pupils in the English education program. In advance, the instructor created a WhatsApp group to use as a teaching resource. To begin the class, the instructor distributed URLs. Podcasting is the center of attention. The podcast's monologue and conversation are chosen by the teacher to present to the class. The pupils read the transcript while also hearing the voice. They go to their electronic dictionary to comprehend the information.  After finishing it, each student was requested to share his thoughts and experiences with the class regarding the subject matter. After the speaker finished speaking, the crowd asked questions that the speaker would respond to.  The teacher then provided feedback when the question-and-answer session was finished. To determine the results, all the data gathered during the treatment was quantitatively examined. It is claimed that the podcast lesson materials help students become more proficient public speakers. These kinds of discoveries can be used by educators to teach the relevant disciplines. It motivates other researchers to carry out relevant research.